2021
DOI: 10.1038/s41467-020-20193-1
|View full text |Cite
|
Sign up to set email alerts
|

Directed transforming of coke to active intermediates in methanol-to-olefins catalyst to boost light olefins selectivity

Abstract: Methanol-to-olefins (MTO), the most important catalytic process producing ethylene and propylene from non-oil feedstocks (coal, natural gas, biomass, CO2, etc.), is hindered by rapid catalyst deactivation due to coke deposition. Common practice to recover catalyst activity, i.e. removing coke via air combustion or steam gasification, unavoidably eliminates the active hydrocarbon pool species (HCPs) favoring light olefins formation. Density functional theory calculations and structured illumination microscopy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 60 publications
3
63
0
1
Order By: Relevance
“…To further investigate the spatiotemporal evolution of organic compounds formed during the MTO conversion, the high-resolution structured illumination microscopy (SIM) was also employed. Following the previous research results 17 , 47 51 , the characteristic UV-vis signals of benzene- (B + ) and naphthalene-based (N + ) carbenium ions should appear at about 390 and 480 nm, respectively, and those of phenanthrene- (PH + ) and pyrene-based (PYR + ) carbenium ions appear at ~560 and ~640 nm, respectively. Thereupon, distinguishable emission wavelengths in the range of 480–490, 500–520, 620–630, and 670–700 nm are expected for the aforementioned carbenium ions, respectively.…”
Section: Resultssupporting
confidence: 70%
“…To further investigate the spatiotemporal evolution of organic compounds formed during the MTO conversion, the high-resolution structured illumination microscopy (SIM) was also employed. Following the previous research results 17 , 47 51 , the characteristic UV-vis signals of benzene- (B + ) and naphthalene-based (N + ) carbenium ions should appear at about 390 and 480 nm, respectively, and those of phenanthrene- (PH + ) and pyrene-based (PYR + ) carbenium ions appear at ~560 and ~640 nm, respectively. Thereupon, distinguishable emission wavelengths in the range of 480–490, 500–520, 620–630, and 670–700 nm are expected for the aforementioned carbenium ions, respectively.…”
Section: Resultssupporting
confidence: 70%
“…It has been shown previously, too, both experimentally and theoretically, that 4MB undergoes dealkylation via the side-chain route of the aromatic cycle to yield ethylene whereas 5MB and 6MB undergo dealkylation via the pairing route of the aromatic cycle to give propylene [3,40,44,85]. The presence of naphthalenes has also been associated with improved ethylene formation [86]. However, none of these conditions (concentration of naphthalenes or 4MB/(5MB+6MB)) alone explained the differences observed in product distributions.…”
Section: Relationships Between Effluent Product and Retained Hydrocarbons Selectivitymentioning
confidence: 92%
“…This process can be performed in different ways, e.g., air combustion (e.g., oxidation with air) and steam gasification (e.g., with H 2 O). 7 In their recently published paper, Zhou and co-workers 8 show that regeneration processes can be used to enhance the catalytic selectivity toward ethylene by transforming coke molecules into active naphthalenic cations. With density functional theory (DFT) calculations, it was shown that these naphthalenic cations are stable in the CHA cages at high temperatures because of spatial confinement.…”
Section: Transforming Inactive Coke Molecules Into Active Intermediat...mentioning
confidence: 99%
“…Further research on the evident differences between the two regeneration methods could Figure 1. Schematic representation of the developed catalyst regeneration approach to transform coke-like molecules into active HCP intermediates in a SAPO-34 molecular sieve This method, as described by Zhou et al 8 in Nature Communications, is visualized by the blue figures. Proposed catalyst regeneration approaches for further studies could aim for the transformation of coke deposits into aromatic intermediates by using gentler conditions (air combustion) or CO 2 to limit environmental contributions.…”
Section: Transforming Inactive Coke Molecules Into Active Intermediat...mentioning
confidence: 99%